The twins at St Clare's - Blyton, Enid. (b, 2013)
Pat(ricia) and Isabel O'Sullivan are identical twins - they want to go to a really expensive school but their parents decide to send them to St Clare's instead. So the two decide to do as worse as possible.
Keywords: St Clare's (Imaginary place) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Boarding schools